2022
DOI: 10.1007/s10461-022-03859-3
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket Expenses and Time Spent on Clinic Visits Among HIV Pre-exposure Prophylaxis Users and Other Clinic Attendees in Eswatini

Abstract: User costs constitute a barrier to the uptake of HIV pre-exposure prophylaxis (PrEP), but their magnitude appears rarely assessed. In this prospective observational study, we assessed self-reported out-of-pocket expenses (OOPE) and time spent on clinic visits during a PrEP demonstration project in Eswatini. At six public primary care clinics, 240 PrEP users and other clinic attendees were interviewed after a clinic visit. Among the 79.2% of clinic attendees reporting any medical OOPE (e.g., expenses for consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In addition to supply-side barriers, including policies limiting PrEP access to narrowly defined groups, subsequent research has identified numerous demand-side barriers to oral PrEP uptake and continuation among women and girls. These include stigma related to sexual activity (especially among adolescent girls) [ 12 , 13 ], assumptions around one’s HIV status related to taking antiretrovirals [ 14 ], pill burden [ 15 , 16 ], the need for regular clinic visits [ 17 , 18 ], low perceived risk of HIV [ 19 , 20 ], and service delivery largely centralized in HIV, STI, or key-population-focused clinic spaces and programs where girls and women don’t often seek care [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to supply-side barriers, including policies limiting PrEP access to narrowly defined groups, subsequent research has identified numerous demand-side barriers to oral PrEP uptake and continuation among women and girls. These include stigma related to sexual activity (especially among adolescent girls) [ 12 , 13 ], assumptions around one’s HIV status related to taking antiretrovirals [ 14 ], pill burden [ 15 , 16 ], the need for regular clinic visits [ 17 , 18 ], low perceived risk of HIV [ 19 , 20 ], and service delivery largely centralized in HIV, STI, or key-population-focused clinic spaces and programs where girls and women don’t often seek care [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In-clinic PrEP care faces several challenges that stem from the recommended frequency of monitoring visits (every 3 months). Clients might have to take time off from work, school, or family obligations, and may incur travel costs for attending in-clinic visits [13][14][15][16][17]. Persons interested in PrEP may also feel burdened with perceived stigma [18,19], cultural or social insensitivity [16,20,21], and lack of privacy [14,15] at the clinic.…”
Section: Introductionmentioning
confidence: 99%